Implementing the 3-omega technique for thermal conductivity measurements - Hänninen, Tuomas (2013)
Thermal conductivity of the constituent materials is one of the most important properties affecting the performance of micro- and nanofabricated devices. These devices often make use of thin films with thicknesses ranging from some nanometers to few micrometers. The thermal conductivity of thin films can be measured with the three-omega method. In three-omega technique a metal wire acting as a resistive heater is microfabricated on the sample. Alternating current passing through the metal heater at a frequency ω heats the sample periodically and generates oscillations in the resistance of the metal line at a frequency 2ω. The oscillating resistance component is coupled with the driving current to create a third harmonic (3ω) voltage component over the heater. The magnitude and frequency dependence of the 3ω voltage can be used to obtain the thermal properties of the sample. The measurement setup consisted of a vacuum chamber with a custom sample mount, lock-in amplifiers to supply the voltage and to record the output, and various other electrical components. Custom LabVIEW programs were used for data acquisition and input signal modification. The goal of the project was to build and validate a 3ω-measurement setup by measuring the thermal conductivities of 300 nm thick SiO2 thin films. Bismuth and gold were used as the heater materials because they have noticeable temperature coeffcients of resistivity, bismuth even at temperatures of a few kelvin. Data analysis revealed that the output of the examined measurement setups can not be used to calculate the thermal properties of the samples. This is most probably due to spurious 3ω-signal in the measurement circuit, originating from the components and voltage sources.